2022
DOI: 10.1038/s41598-022-20527-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome insights from 16S rRNA analysis of 17-year periodical cicadas (Hemiptera: Magicicada spp.) Broods II, VI, and X

Abstract: Periodical cicadas (Hemiptera: Magicicada) have coevolved with obligate bacteriome-inhabiting microbial symbionts, yet little is known about gut microbial symbiont composition or differences in composition among allochronic Magicicada broods (year classes) which emerge parapatrically or allopatrically in the eastern United States. Here, 16S rRNA amplicon sequencing was performed to determine gut bacterial community profiles of three periodical broods, including II (Connecticut and Virginia, 2013), VI (North Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A greater sampling of nymphal gut microbial diversity and abundance is needed to understand the contribution of environmentally acquired microbiota in the much longer-lived nymphal stage, as well as the microbes that are transmitted to the adult stage from the nymphal stage. Previous work has shown that Magicicada nymphs had gut microbial communities that differed from both the adults and the soil in which they were found 67 . While the lack of microbial diversity in eggs dissected from the abdomens of female cicadas in this study suggests a lack of vertical transmission of non-endosymbiotic bacteria, both the overwhelming relative abundance of cicada endosymbiont cells and the lack of other bacterial cells in these samples may prevent detection of low-abundance microbes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A greater sampling of nymphal gut microbial diversity and abundance is needed to understand the contribution of environmentally acquired microbiota in the much longer-lived nymphal stage, as well as the microbes that are transmitted to the adult stage from the nymphal stage. Previous work has shown that Magicicada nymphs had gut microbial communities that differed from both the adults and the soil in which they were found 67 . While the lack of microbial diversity in eggs dissected from the abdomens of female cicadas in this study suggests a lack of vertical transmission of non-endosymbiotic bacteria, both the overwhelming relative abundance of cicada endosymbiont cells and the lack of other bacterial cells in these samples may prevent detection of low-abundance microbes.…”
Section: Discussionmentioning
confidence: 98%
“…Lack of stable microbial communities in New Zealand cicadas. Studies of plant sucking bugs with specialized bacteriome-dwelling endosymbionts have with few exceptions 21,67 not focused on the microbiota outside the bacteriome. Our dataset suggests that adult cicadas have low abundance transient microbial communities in their guts as shown in some other insects 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…This was an expected result due to the difficulties in culturing many endosymbiotic bacteria in axenic culture media [ 17 ]. Indeed, numerous endosymbionts inhabiting insects rely on their host and other microbial community members for metabolic functions and development [ 36 ]. To mimic the chemical composition of the insect host, we supplemented a primary medium (PCA) with crushed insects or commercial insect medium.…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA-seq of metagenome can be used to identify dominant microorganisms present in biological samples, and it is an accurate method to detect microbial infection without culture [25]. Most of the previous studies have investigated the interaction between insects and gut microflora through 16S rRNA-seq, such as cicadas [26], mosquitoes [27], and fruit flies [28]. The reproductive mode of T. pretiosum infected with PI Wolbachia will be changed to varying degrees by exposure to antibiotics and high temperatures [4,16].…”
Section: Introductionmentioning
confidence: 99%